Disruptions of Sustained Spatial Attention Can Be Resistant to the Distractor’s Prior Reward Associations - Bachman, Matthew D.; Hunter, Madison N.; Huettel, Scott A.; Woldorff, Marty G. (Frontiers in Human Neuroscience, 2021)
Attention can be involuntarily biased towards reward-associated distractors (value-driven attentional capture, VDAC). Yet past work has primarily demonstrated this distraction phenomenon during a specific set of circumstances: transient attentional orienting to potentially relevant stimuli occurring in our visual environment. Consequently, it is not well-understood if reward-based attentional capture can occur in other settings, such as during sustained visuospatial attention. Using EEG, we investigated whether associating transient distractors with reward value would increase their distractibility and lead to greater decrements in concurrent sustained spatial attention. Human participants learned to associate three differently colored, laterally presented squares with rewards of varying magnitude (zero, small, large). These colored squares were then periodically reintroduced as distractors at the same lateral locations during a demanding sustained-attention rapid-serial-visual-presentation (RSVP) task at the midline. Behavioral and neural evidence indicated that participants had successfully learned and maintained the reward associations to the distractors. During the RSVP task, consistent with prior work, we found that the distractors generated dips in the instantaneous amplitude of the steady-state visual evoked potentials (SSVEPs) elicited by the midline RSVP stimuli, indicating that the distractors were indeed transiently disrupting sustained spatial attention. Contrary to our hypotheses, however, the magnitude of this dip did not differ by the magnitude of the distractor’s reward associations. These results indicate that while sustained spatial attention can be impaired by the introduction of distractors at another location, that the main distraction process is resistant to the distractors’ reward associations, thus providing evidence of an important boundary condition to value-driven attentional capture.